White blood cell count and ratio changes in newborns after granulocyte colony-stimulating factor treatments - Melek Buyukeran; Åžule YiÄŸit; Hasan Tolga Çelik; Murat Yurdakök (Indonesian Pediatric Society, 2021)
Background Granulocyte-colony stimulating factor (G-CSF) is frequently used to treat neonatal neutropenia. There is a paucity of data in the literature on when immature to total neutrophil ratio (I/T ratio) can be accurately used as a sepsis marker after G-CSF therapy, as well as when I/T ratio returns to normal values expected in newborns who did not receive G-CSF. Objective To investigate changes in white blood cells counts and ratios in neonates with neutropenia before and after G-CSF therapy. Methods This retrospective study included newborns admitted to the NICU of Hacettepe University Ihsan Dogramaci Hospital, Ankara, Turkey, between 2005 and 2017 who received G-CSF therapy for neutropenia. Subjects underwent complete blood counts on the day before receiving G-CSF therapy (day 0) as well as days 1, 2, and 3 after treatment; I/T ratios were recorded from peripheral smears. Results Twenty-eight neonates were included in the study. Subjects’ median gestational age (interquartile range 25–75%) was 32.6 (29.7–37.6) weeks, and median birth weight was 1,630 (1,040–2,980) g. On day 3, there were significant increases in white blood cell counts compared to day 0. There were statistically significant elevations in the I/T ratios between day 0 and day 1 and between day 0 and day 2. On day 3, the I/T ratio decreased, but was not significantly different between day 0 and day 3. Conclusion The changes in I/T ratio observed after G-CSF treatments in our study suggest that the I/T ratio can be used as a reliable sepsis marker starting 72 hours after G-CSF administration. However, I/T ratio is significantly affected within 72 hours of G-CSF administration, and therefore, is unreliable as a sepsis marker during that period.